(untitled) (Al-Academy, 2016)
Brainstorming is considered as one of the manners that develop learners’ mental abilities. Besides, it can help learners get a lot of ideas and thoughts. And by following applied steps to answer the problem concerned, the researcher carried out this practical study aimed at:Developing the ideas of design of third year students/Institute of Fine Arts/Evening Studies- Baghdad/First Rusafa by employing Brainstorming mechanism to develop the ideas of design of institute students in designing the technical advertisement and to achieve the authenticity of the goal of the research, Department of Plastic Arts/Institute of Fine Arts/Evening Studies/Baghdad-First Rusafa was chosen as a case study for the research. It embraced (20) students who represents (100%) of the original case study. They are distributed in two groups (T and D). And each group embraces (10) students following achieving the balance among them in each group of learners of Design and Decoration Subject/Third Stage/ (2014 - 2015) Academic Year. Besides, Group T students were exposed to brainstorming mechanism through applied lessons prepared by both researchers whereas, group D was taught normally. Students of both groups were exposed to pre-test and post-test. After that, data were collected and processed statistically by the use of (t-test) to make sure of the authenticity of hypotheses that were prepared for the purpose concerned and the results are presented as follows:The goal achieved as a result of brainstorming mechanism effectively in developing the ideas of design in designing the technical advertisement concerning mental factors within the technical results such as (sensitivity towards problems, ease, flexibility and authenticity) they were in favour of group T which was taught in accordance with brainstorming mechanism in presenting applied lessons which achieved the employment of the relations of designs in designing the idea and applying it within the terms of design of technical advertisement. As for the most important results, the development of learners mental abilities in producing many diversified ideas of design can be gathered in educational lessons depending on brainstorming mechanism. Then, it can be developed if all conditions are appropriate. Finally, both researchers recommend adopting brainstorming mechanism in generating and developing the ideas of design as an assistant factor for instructor through teaching